Unlocking The Potential of Coban Canggu as a Nature Tourism Destination In Mojokerto Regency - Muhammad Bilal Baslum; I Komang Astina; Yuswanti Ariani Wirahayu; Waode Yunia Silviariza; Ibrahim Ibrahim; Shida Irwana Binti Omar (Universitas Negeri Gorontalo, 2025)
This research aims to unlock the potential of Coban Canggu, a waterfall attraction, as one of the nature tourism destinations in Mojokerto Regency, Indonesia. The main objective of the study is This study aims to evaluate tourist attractions and provide recommendations for improving underdeveloped aspects to enhance the competitiveness of Coban Canggu as a leading tourist destination in East Java. Located in Pacet Village, Coban Canggu is known for its crystal clear waterfall, and beautiful scenery, easily accessible, and within the vicinity of other attractions. The study employed a mixed-method approach and gathered data through questionnaire surveys, field observations, and a literature review. Survey data was drawn from 40 visitors and a tourism manager in the study area using a random sampling technique. The ADO-ODTWA guidelines, provided by the Indonesian Department of Forestry, were used to evaluate the tourism potential of the study area. The findings reveal that Coban Canggu achieved an index of 73.7%, indicating the area is highly suitable for future tourism development. The key strengths of the area include its natural charm, diverse tourism activities, sufficient tourism accommodations, and accessibility. However, the site also faces challenges such as inadequate water supply, suboptimal cleanliness, and poor management practices that hinder its full potential. The site’s cleanliness is affected by limited waste management facilities and visitor behavior, while water supply remains insufficient and poorly managed. The research emphasizes the importance of improving infrastructure and facilities, optimizing management practices, and implementing sustainable tourism strategies. In addition, enhancing the promotion and integrating other attractions or services are recommended to boost its competitiveness. In conclusion, the study highlights Coban Canggu’s potential as significant and vital towards regional economic growth and tourism development, while advocating for sustainable practices to preserve its environmental and cultural value.